EFFECT OF CUTTING SPEED IN THE TURNING PROCESS OF AISI 1045 STEEL ON CUTTING FORCE AND BUILT-UP EDGE (BUE) CHARACTERISTICS OF CARBIDE CUTTING TOOL - Sobron Yamin Lubis; Sofyan Djamil; Yehezkiel Kurniawan Zebua (SINERGI, 2020)
In the machining of metal cutting, cutting tools are the main things that must be considered. Using improper cutting parameters can cause damage to the cutting tool. The damage is Built-Up Edge (BUE). The situation is undesirable in the metal cutting process because it can interfere with machining, and the surface roughness value of the workpiece becomes higher. This study aimed to determine the effect of cutting speed on BUE that occurred and the cutting strength caused. Five cutting speed variants are used. Observation of the BUE process is done visually, whereas to determine the size of BUE using a digital microscope. If a cutting tool occurs BUE, then the cutting process is stopped, and measurements are made. This study uses variations in cutting speed consisting of cutting speed 141, 142, 148, 157, 163, and 169 m/min, and depth of cut 0.4 mm. From the results of the study were obtained that the biggest feeding force is at cutting speed 141 m/min at 347 N, and the largest cutting force value is 239 N with the dimension of BUE length: 1.56 mm, width: 1.35 mm, high: 0.56mm.